UJI DAYA ANTIBAKTERI SARI PATI DAUN RUKAM (Flacourtia rukam) TERHADAP ZONA HAMBAT Escherichia coli - Desmi Viana Putri; Fitria Lestari; Mareta Widiya (Jurnal Biosilampari : Jurnal Biologi, 2019)
Escherichia coli is a microscopic gram-negative bacteria that in the human digestive system and is one of the causes oof diarrheal disease. Treatment of dearrheal diseases usually uses chemical drugs. Chemical drugs are believed to have excessiive side effects. This can be replaced with a drug that has a low side effect in the from of traditional medicine. One plant that can be used as a medicine for diarrhea is rukam (Flacourtia rukam). Rukam (Flacourtia rukam) is a plant that has properties as an antibacterial drug. The compounds contained in rukam (Flacourtia rukam) include flavanoids, saponins, tannins, and alkaloids. The aim of this study was to determine the antibacterial strength of the extract of rukam (Flacourtia rukam) leaf starch againt the Escherichia coli inhibition zone. The results obtained that rukam (Flacourtia rukam) has a different inhibitory zone, from various concentrations of 4%, 6%, 8%, 10%. Concentration with the highest inhibition zone is a concentration of 10%.